2021
DOI: 10.1108/ilt-03-2021-0083
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the influence of friction pair material hardness on the tribological behaviors of water lubricated thrust bearings

Abstract: Purpose This paper aims to confirm that increasing the hardness of thrust collars can improve the load carrying capacity (LCC) and wear resistance of water lubricated thrust bearings (WTBs) made of polymers paired with non-polymeric thrust collars, and to design a WTB with high LCC and durability for a shaftless pump-jet propulsor of an autonomous underwater vehicle. Six kinds of WTBs were manufactured by matching aluminum bronze, stainless steel and silicon nitride with two different polymer bearing materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Nevertheless, the mean wear rate increases sharply when the load exceeds 300 N. The mean wear rate reaches 8.03 × 10 −9 kg/(N −1 ×m −1 ) when the load is applied up to 500 N. The binding force between aluminum bronze matrix and solid lubrication film is weak. When the load becomes large, the lubrication film will be damaged, thus the wear amount is greatly increased (Liang and Yang, 2021). The result shows that the aluminum bronze inlaid type does not maintain good wear characteristics under higher loads.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the mean wear rate increases sharply when the load exceeds 300 N. The mean wear rate reaches 8.03 × 10 −9 kg/(N −1 ×m −1 ) when the load is applied up to 500 N. The binding force between aluminum bronze matrix and solid lubrication film is weak. When the load becomes large, the lubrication film will be damaged, thus the wear amount is greatly increased (Liang and Yang, 2021). The result shows that the aluminum bronze inlaid type does not maintain good wear characteristics under higher loads.…”
Section: Resultsmentioning
confidence: 99%
“…After further friction, the metal abrasive particles embedded in the surface of the polymer material would appear hardening effect, and then grinding with the metal surface of the friction pair like "sandpaper". Two-body abrasive wear is converted into three-body abrasive wear [207], forming a so-called "soft wear hard".…”
Section: Main Wear Forms Of Wlbsmentioning
confidence: 99%
“…| https://mc03.manuscriptcentral.com/friction morphology of the thrust ring with aluminum bronze/Throden SXL friction pairs [86] and compared the wear results with stainless steel/PEEK friction pairs [209], which concluded that harder frictional subsets could increase the loading capacity of thrust bearings and reduce wear. Therefore, six sets of friction pairs with different hardness combinations as shown in Table 7 were tested and the results indicated that the increasing hardness of thrust rings would reduce the production possibility of abrasive particles and improve wear resistance [207].…”
Section: Frictionmentioning
confidence: 99%
“…At the microscopic level, the peaks between the shaft and bearing are close together, resulting in high friction between the surfaces. During this stage, the changes in the friction mainly rely on the bearing material's performance impact [90,148,149]. Over time, the lubricant film gradually forms, reducing friction between the two surfaces.…”
Section: Analysis Of Bearing Lubrication Statusmentioning
confidence: 99%